Percutaneous nephrostomy drainage: A primary salvage drainage procedure and restoration of renal function in cases oof obstructive uropathy. - Sharma, Uttam Kumar (1999)
SUMMARY: A prospective study was undertaken at the Department of Surgery, Tribhuvan University Teaching Hospital (TUTH) IN PATIENTS WITH OBSTRUCTIVE UROPATHY. Their return of unit renal functions was studied after the upper urinary diversion in the form of percutaneous nephrostomy (PCN). Diagnosis of obstructive uropathy was made on the basis of their clinical sign and symptoms of uraemia , pain in the login, intravenous urography (IVU), ultrasonography (USG) and blood biochemistry for renal function test. percutaeous nephrostomy was performed in 50 cases (61 Renal units) with obstructive uropathy at the Department of surgery. Trivhuvan University Teaching Hospital between April 1996 and January 1998. Most of the patients (64%) were presented with pain and swelling in loin, 22% of the cases had ower urinary tract symtoms. Fever and uraemic symptoms were found to be 20% and 16% respectively. Urinary stones disease were found to be the most common cause of urinary outflow obstruction (72%) followed by pelvi-uretery junction (PUJ) obstruction in 26%. Stent dislodgement and blockage were the most common complications (36%0 noted after the PCN. Fulminating septicaemia with fatal outcome was recorded in 3 cases. Improvement of unit renal function was recorded in 54 renal units (88.5%) after the success ful PCN drainage during the period of 3-4 weeks. Their serum creatinine level were markedly reduced to normal of near normal in 48%, who had bilateral obstructive uropathy or had solitary obstructed kidney. Their unit renal output through PCN tube was significantly improved (>400ml/day)in 86.6%. Definitive surgery was conducted in 80.3% of cases after the successful PCN drainage, while 7 cases (11.47%) needed nephrectomy because they did not show any improvement in renal function even after six weeks of follow up. It is concluded that PCN is an ideal, effective and safe drainage procedure in cases with obstructive uropathy when their renal function is doubtful in conventional IVU series. It has minimal correctable complications. It not only decompresses the nonfunctioning. This a never modality is needed to assess the split renal function in our contest where radio isotope renogram is not frequently available. Percutaneous nephrostomy (PCN) is a simple radiological procedure started since 1970(1) by chich obstruction can be relieved temporarily by interesting a multiholed tube inside the renal pelvis through the lion skin to the renal parenchyma with the help of USG or Fluroscopy X-rays. It is sometimes life saving procedure in uraemicpatients when both or solitary functioning kidney is obstructed. It is well known to all and proved by several studies (2,3,4 and 5) that PCN is an important primary drainage procedure for benign or malignant obstructive uropathies. Previously, indication of PCN was very limited, since the development of newer radio technology the use of PCN has broadened. Nowadays PCN is not only used for decompressing the hydronephrotic or pyonephrotic kidney but it also has diagnostic or therapeutic values like antegrade pyelography ( Appendix : Photo A) , pressure study of the renal pelvis (Whitaker test), removal of foreign bodies or stones percutaneous nephrostomy lithotripsy(PCNL) or endopyelotomy.